Without offending humans : a critique of animal rights - Fontenay, Élisabeth de (Posthumanities, 2012)
This study pursues the investigation Fontenay began in her magnum opus, 'The Silence of the Beasts: Philosophy Confronts Animality' with a series of essays of somewhat more topical reach. Fontenay's perspective is resolutely informed by Continental Philosophy, which brings her to articulate a very strong critique of the pragmatist frame through which animal rights are often defended. Fontenay seeks to maintain the anthropological difference between man and animal that Singer and Cavalieri openly and brazenly, upon Fontenay's account, ignore.